ATTITUDES TOWARDS DOPPING AND PERFECTIONISM IN SOCCER, INDOOR SOCCER, AND BASKETBALL PROFESSIONAL ATHLETES IN COSTA RICA - Salas-Ramírez, Karen (2018)
The purpose of the present study was to evaluate the attitude toward doping and its relationship with perfectionism in professional athletes from three sports in Costa Rica. Through questionnaires, the attitude towards doping and its relationship with perfectionism was evaluated in 217 professional athletes over 18 years of age, 121 were men and 96 women. They were enrolled in the top-elite championship of Costa Rica during the 2013 and 2014 seasons, in the disciplines of soccer, indoor soccer, and basketball. For the attitude towards doping an average of 34.33 ± 11.40 was obtained, while for perfectionism the average was 83.08 ± 12.27. Men presented a significantly more positive (p= 0.001) attitude toward doping and are more perfectionist (p= 0.028) in their sports performance than women. There is a significant positive correlation (p= 0.000) between attitude towards doping and perfectionism in sports. In general, the participants in this study have a negative attitude toward doping. Both in the attitude toward doping and in perfectionism, no differences were found between sports or in the sport-sex interaction. The significant relationship found between perfectionism and the attitude towards doping suggests that an athlete with these perfectionist characteristics might be more prone to incur such practices.